Phenylthiocarbamide perception in epileptic patients on carbamazepine therapy - Hilmy AS Abdul-Jabbar; Isam H.Mahmood; Sabah K AL-Dabbagh; Imad A-J Thanoon (University of Mosul, 2011)
The present study was designed to study the taste sensitivity to phenylthiocarbamide among epileptic patients. A total of ٧٣ epileptic patients participated in the study. The epileptic state of the patients was well controlled by carbamazepine therapy, with their serum level of carbamazepine within therapeutic range. The other group consists of ٦٢ healthy volunteers, serving as a control. Test strips impregnated with phenylthiocarbamide have been used to identify tasters from non tasters of both patients and control groups. The individuals who perceive phenylthiocarbamide as bitter tasting was regarded as tasters while those describe it as tasteless were regarded as non-tasters. The results showed no significant difference with regard perception of phenylthiocarbamide between epileptic patients on carbamazepine therapy and controls.